A 70 years Woman Presented With Pseudomexoma Peritoni Secondary to Primary Ovarian Mucinous Cystadenocarcinoma: A Case Report (Bangladesh Journal of Obstetrics & Gynaecology, 2026)
Pseudomyxoma peritonei (PMP) is a rare and life-threatening condition of the parietal peritoneum that produces abundant mucin or gelatinous ascites. The tumors cause fibrosis of tissues and impaired digestion or organ function, and if left untreated, the tumors and mucin they produce will fill up the abdominal cavity. This will result in compression of organs and will destroy the function of the colon, small intestine, stomach, and other organs. Prognosis with treatment in many cases is optimistic, but the disease is lethal if untreated, with death occurring via cachexia, bowel obstruction, or other types of complications. Symptoms can be non-specific and ignorable for several years such that most cases are diagnosed during explorative surgery.A 70 yrs old woman admitted in Popular Medical College Hospital with anorexia, discomfort with abdominal distention and constipation. She was diagnosed clinically, with the help of CT scan and tumor marker as multi septated large ovarian tumor with incisional hernia. She had past history of ovarian cystectomy 2 years back. After laparotomy huge amount of mucin was found with in the abdominal cavity, probably from ovarian origin and then we had done total abdominal hysterectomy with bilateral salpingo-ophorectomy, appendectomy, removal of all mucin from abdominal cavity with hernia repair. Hystopathologically it was detected as low-grade mucinous cyst adenocarcinoma and she completed 6 cycles chemotherapy. Her oneyear follow up period was completely uneventful. We report an interesting and rare case of Pseudomyxoma peritonei who had undergone successful surgery and post oparetive chemotherapy. She is under regular follow up yearly. She is now symptom and disease free. This case is presented with review of Literature here.Conclusion: It is a rare disease. Reporting the case may help the physician to understand the outcome of pseudomyxoma peritonei. Keywords: Pseudomyxoma peritonei, Mucinous cystadenocarcinoma.Bangladesh J Obstet Gynaecol, 2025; Vol. 40(2): 126-130